2017
DOI: 10.18596/jotcsa.351708
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Al2O3 Supports for Thin Membrane Fabrication

Abstract: Abstract:In this study, macroporous -alumina supports were prepared by using vacuum assisted filtration of α-Al2O3 suspensions with different particle size. The average particle sizes of the powders are 400 and 200 nm. The prepared supports had smooth and uniform surface microstructure and well suited for the fabrication of thin continuous membrane. The microstructure consists of a random close-packing of 200 nm particles led to improved surface uniformity and roughness. ZnO spheres were prepared by homogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Ten years later, Wang et al investigated photoluminescence in their porous monolithic α-Al 2 O 3 prepared by a modified polyacrylamide gel route, finding pore diameters of 80-500 nm [83]. Topuz et al reported pore diameters of 110 nm in macroporous α -alumina supports prepared by using vacuum assisted filtration of α-Al 2 O 3 suspensions [174]. Finally, three articles were published in 2019: Ahmad et al reported on α-Al 2 O 3 from hydrothermally prepared ammonium aluminum carbonate hydroxide whiskers with distinct pore diameters of 260 nm, yet without precisely determining the corresponding pore volume [41].…”
Section: Pure α-Alumina With Pores In the Sub-micrometer Rangementioning
confidence: 99%
“…Ten years later, Wang et al investigated photoluminescence in their porous monolithic α-Al 2 O 3 prepared by a modified polyacrylamide gel route, finding pore diameters of 80-500 nm [83]. Topuz et al reported pore diameters of 110 nm in macroporous α -alumina supports prepared by using vacuum assisted filtration of α-Al 2 O 3 suspensions [174]. Finally, three articles were published in 2019: Ahmad et al reported on α-Al 2 O 3 from hydrothermally prepared ammonium aluminum carbonate hydroxide whiskers with distinct pore diameters of 260 nm, yet without precisely determining the corresponding pore volume [41].…”
Section: Pure α-Alumina With Pores In the Sub-micrometer Rangementioning
confidence: 99%